EFEKTIVITAS PEMBERLAKUAN TARIF PROGRESIF BAGI PAJAK KENDARAAN BERMOTOR GUNA MENINGKATKAN PENERIMAAN PAJAK - Ida Bagus Agung Daparhita; Anak Agung Ayu Tini Rusmini Gorda (Jurnal Analisis Hukum, 2018)
Motor Vehicle Tax (PKB) is one type of tax whose authority of collection is on Provincial government as a form of autonomy implementation. Nevertheless the government through Law no. 28 Year 2009 on Regional Tax and Retribution has been applying progressive tariff for motor vehicle taxation (PKB). Government policy is related to the purpose of increasing local tax revenues from the PKB sector. The provincial government further implements the policy by issuing local regulations concerning the implementation of progressive taxation, among which regulates the amount of tax to be imposed on each motor vehicle. In Bali Province Regulation no. 1 Year 2011 on Regional Taxes, the provincial government of Bali has set the tax rate between 1.5% to 7.5%. In addition to the increase in tax revenues, the progressive tariff for PKB also aims to reduce people's purchasing power on motor vehicles. This is investigates whether it is possible to increase tax revenues when the purchasing power of people to buy motor vehicles goes down. This research is conducted by empirical research method, in order to study the effectiveness of progressive tariff policy for motor vehicle to increase tax revenue from PKB in Bali Province area. This research uses actual data related to the amount of PKB receipt obtained since before the enactment of progressive tariff until several years after. Based on these data, it can be seen the effectiveness of the implementation of the progressive tariff. In addition, it will also convey the obstacles faced by the Bali Provincial Government in implementing the progressive tariff policy of PKB. Thus the research will be able to give description of the enforcement of progressive rate of PKB as well as to formulate suggestions to reduce the constraints of its implementation, especially in the area of Bali Province.Keywords: Revenue, Progressive Rate, Motor Vehicle.